2010
DOI: 10.1165/rcmb.2008-0335oc
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Tuberin Promotes Cell Invasion through the β-Catenin Pathway

Abstract: Mutations in the tumor suppressor tuberin (TSC2) are a common factor in the development of lymphangioleiomyomatosis (LAM). LAM is a cystic lung disease that is characterized by the infiltration of smooth muscle-like cells into the pulmonary parenchyma. The mechanism by which the loss of tuberin promotes the development of LAM has yet to be elucidated, although several lines of evidence suggest it is due to the metastasis of tuberin-deficient cells. Here we show that tuberin-null cells become nonadherent and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…Furthermore, previous studies in PC12 cells reported the ability of Wnt to increase b-catenin levels and cell proliferation only upon application of the ligand or overexpression of Wnt, its frizzled receptors or the intracellular effector dishevelled (Chou et al, 2000;Kaliwara et al, 2008;Chacòn et al, 2008;Spinsanti et al, 2008), which is not the case in our study. Thus, our data suggest that, as previously reported in other cell systems (Mak et al, 2003;Jozwiak and Wlodarski, 2006;Barnes et al, 2010), a decrease of TSC2 hinders the stability of the GSK3b complex and hence favors the decreased degradation and nuclear translocation of b-catenin, with ensuing strengthening of its transcriptional activity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, previous studies in PC12 cells reported the ability of Wnt to increase b-catenin levels and cell proliferation only upon application of the ligand or overexpression of Wnt, its frizzled receptors or the intracellular effector dishevelled (Chou et al, 2000;Kaliwara et al, 2008;Chacòn et al, 2008;Spinsanti et al, 2008), which is not the case in our study. Thus, our data suggest that, as previously reported in other cell systems (Mak et al, 2003;Jozwiak and Wlodarski, 2006;Barnes et al, 2010), a decrease of TSC2 hinders the stability of the GSK3b complex and hence favors the decreased degradation and nuclear translocation of b-catenin, with ensuing strengthening of its transcriptional activity.…”
Section: Discussionsupporting
confidence: 86%
“…Although the complex, by its binding to the small GTPase Rheb, inhibits mTORC1, it promotes mTORC2 signaling (Huang et al, 2008;Huang and Manning, 2009;Laplante and Sabatini, 2009). In addition, the TSC1-TSC2 complex can have an impact on cell proliferation through its positive control of the turnover of b-catenin (Mak et al, 2003;Jozwiak and Wlodarski, 2006;Barnes et al, 2010). We thus investigated the expression of the TSC complex and b-catenin in wtPC12 and PC12-27 cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, an ϳ70-kDa truncated ␤-catenin expressed by the Tsc2-null cells was shown to be a strong coactivator of MMP7 transcription, and the secreted MMP7 promoted their invasive behavior. 34 These observations fit nicely with the role of TSC2 in EMT. Because mTORC1 is frequently activated in human cancers, the relevance of our finding deserves further investigation in the context of tumor invasion and metastasis in general.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, we recently reported that the nonadherent Tsc2-null cells acquire an invasive phenotype that is mediated via ␤-catenin-dependent, matrix metalloproteinase (MMP) 7 activity. 34 As the Tsc2(Ϫ/Ϫ) cells detach, ␤-catenin undergoes caspase-dependent cleavage, resulting in transcriptionally active products. For example, an ϳ70-kDa truncated ␤-catenin expressed by the Tsc2-null cells was shown to be a strong coactivator of MMP7 transcription, and the secreted MMP7 promoted their invasive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelioid cells also express the melanocytic marker gp100, which reacts with the human melanin black antibody HMB-45, and spindle cells express the proliferation cell nuclear antigen [30]. LAM cells also express estrogen and progesterone receptors [30], matrix metalloproteinases (MMP) [31], vascular endothelial growth factor receptor 3 [32-35], β-catenin and E-cadherin [36, 37], CD44v6, an adhesion molecule associated with metastatic behavior [38], and chemokines and chemokine receptors involved in homing of LAM cells to specific organs [39, 40]. LAM nodules contain cleft-like spaces lined by lymphatic endothelial cells, which express lymphangiogenic factors and their receptors [41].…”
Section: Lam and Tuberous Sclerosismentioning
confidence: 99%